Faz essa equaçao do 2 grau toda pra mim fazendo favor
2x+x²-15=0

1
x² + 2x - 15 = 0
∆ = (2)² - 4*1*(- 15)
∆ = 4 + 60
∆ = 64

x = - (2) ± √64 / 2*1
x = - 2 ± 8 / 2
x' = - 2 + 8 / 2
x' = 3

x'' = - 2 - 8 / 2
x'' = - 5

Resposta : x' = 3 e x'' = - 5

Respostas

2014-06-08T19:34:29-03:00
X² + 2x - 15 = 0
∆ = (2)² - 4*1*(- 15)
∆ = 4 + 60
∆ = 64

x = - (2) ± √64 / 2*1
x = - 2 ± 8 / 2
x' = - 2 + 8 / 2
x' = 3

x'' = - 2 - 8 / 2
x'' = - 5

Resposta : x' = 3 e x'' = - 5

Duvidas chame no Wats: 6181913393